2016
DOI: 10.1530/joe-15-0510
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary exercise improves hypothalamic and metabolic function in obese mice

Abstract: Exercise plays a critical role in regulating glucose homeostasis and body weight. However, the mechanism of exercise on metabolic functions associated with the CNS has not been fully understood. C57BL6 male mice (n = 45) were divided into three groups: normal chow diet, high-fat diet (HFD) treatment, and HFD along with voluntary running wheel exercise training for 12 weeks. Metabolic function was examined by the Comprehensive Lab Animal Monitoring System and magnetic resonance imaging; phenotypic analysis incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 41 publications
4
49
0
6
Order By: Relevance
“…Exercise is a powerful antiobesity tool, with several studies indicating that exercise can have positive outcomes through affecting epigenetics (Brown, ; Nitert et al, ; Ronn et al, ). In a study using mice, it was reported that exercise had positive effects on restoring POMC action impaired by HFD (Laing et al, ). It would be interesting to investigate whether this effect was achieved through modulation of POMC DNA methylation patterns.…”
Section: Lifestyle Modification Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise is a powerful antiobesity tool, with several studies indicating that exercise can have positive outcomes through affecting epigenetics (Brown, ; Nitert et al, ; Ronn et al, ). In a study using mice, it was reported that exercise had positive effects on restoring POMC action impaired by HFD (Laing et al, ). It would be interesting to investigate whether this effect was achieved through modulation of POMC DNA methylation patterns.…”
Section: Lifestyle Modification Interventionsmentioning
confidence: 99%
“…In a study using mice, it was reported that exercise had positive effects on restoring POMC action impaired by HFD (Laing et al, 2016). It would be interesting to investigate whether this effect was achieved through modulation of POMC DNA methylation patterns.…”
Section: Life S T Yle Modific Ation Interventi On Smentioning
confidence: 99%
“…A growing body of evidence has demonstrated that exercise is an effective therapeutic intervention for treating obesity and the related secondary complications [10,11]. Intriguingly, voluntary exercise gives rise to anti-inflammatory effects against fat-rich diet-induced hypothalamic inflammation [10,12]. However, the endocrine substances that mediate the benefits of exercise are yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Knowing APPL1 activates PI3K protein (Cleasby et al., ), we hypothesize this mechanism may occur in the central nervous system (CNS), especially in the hypothalamus, an important structure responsible for the food intake control. As a non‐pharmacological strategy, physical exercise has positive effects on the control of hypothalamic disorders and food intake (Laing et al., ; Rodrigues et al., ; Ropelle et al., ).…”
Section: Introductionmentioning
confidence: 99%